2014
DOI: 10.1016/j.jcrs.2014.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Biometry and corneal astigmatism in cataract surgery candidates from Southern China

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
69
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 19 publications
22
69
10
2
Order By: Relevance
“…Studies on the Chinese population in Singapore [12], indigenous communities in Alaska [13] and the Caucasian population in Iceland [14] have shown that AL has a negative correlation with age; In spite of the negative correlation between AL and patient age, our results introduced anterior chamber depth as a robust marker to be positively correlated with age. In the current study, all variables and the corneal power were normally distributed in the population, which differs from the results of previous studies [15]. The mean AL in the Chinese study was longer than in the current and some previous studies and appears to be closely associated with genetic and environmental Factors [16].…”
Section: Discussioncontrasting
confidence: 99%
“…Studies on the Chinese population in Singapore [12], indigenous communities in Alaska [13] and the Caucasian population in Iceland [14] have shown that AL has a negative correlation with age; In spite of the negative correlation between AL and patient age, our results introduced anterior chamber depth as a robust marker to be positively correlated with age. In the current study, all variables and the corneal power were normally distributed in the population, which differs from the results of previous studies [15]. The mean AL in the Chinese study was longer than in the current and some previous studies and appears to be closely associated with genetic and environmental Factors [16].…”
Section: Discussioncontrasting
confidence: 99%
“…The mean preoperative astigmatism was 1.27 ± 0.64 D. These results are higher than those reported by Gokhale et al [17] in their work on the manual and sutureless small incision cataract surgery (MSICS) and the induction of astigmatism that was 0.50 D. Our results are similar to those of Isyaku et al [18] in Nigeria who reported a mean astigmatism of 1.16 D. Also, the axis of preoperative astigmatism was indirect in 48% of cases. Our results are similar to those of some authors who have found that most senile cataract patients have an indirect astigmatism whose incidence increases with age, especially after 50 years [19][20][21][22][23]. Sanfilippo et al [21] reported a mean frequency of significant astigmatism among those aged 70 and over in 55.1% with extremes of 47.2 and 62.7%.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with the other studies our results are slightly lower except Ferrer-Blasco et al's study (34.8%). 11,[12][13][14][15] In addition to these, the study from our country with a limited sample reports ratio of the astigmatism equal or higher than 1 D was 29.7%. 16 The reason for the differences of our study can be racial factors (other country based studies) and regional or sample size origin (our country based study).…”
Section: Age Groups (Years)mentioning
confidence: 57%
“…Mean corneal astigmatism in our study (1.03±0.9) is similar to previous studies. [10][11][12][13][14] In our sample 63.24% of the eyes have less than 1 D astigmatism. This eyes may have benefit from techniques described above.…”
Section: Age Groups (Years)mentioning
confidence: 60%
See 1 more Smart Citation